FRODO'S RING OF FRIENDSHIP IN PETER JACKSON'S THE LORD OF THE RING MOVIE (2001): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - SUKMA, OKTA PRAMITA (2011)
This research paper elaborates Frodo's Ring of Friendship in Peter Jackson's The Lord of the Ring Movie (2001) that is analyzed through individual psychological approach. The objectives of the research are to analyze the structural elements of the movie and to analyze the movie based on individual psychological approach. This research belongs to a descriptive qualitative research. The data of the research is the movie entitled The Lord of the Ring: The fellowship of the Ring whereas the data source comes from both primary data source which is in the form of the script of the movie being researched and secondary data source related to the research as some books of individual psychological theories, internet and other relevant information. The study comes to the following conclusion. First, based on the structural analysis, it is evident that in this movie Peter Jackson wants to convey a moral message that friendship is one of the way to get success for a job and struggle for better life is one effort to get a change for happiness in the life. Second, based on the individual psychological analysis, it is evident that in this movie Frodo is as the major character. He hopes that he can finish his job on the quest to destroy the one ring on Mordor to save the earth from the darkness and wants to get happiness in the future of life without the burden as the bearer of the ring again.